Conditioning and coordination motor abilities of taekwondo ITF athletes - Litwiniuk, A. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Conditioning and coordination motor abilities (CMA) play a very important role in the process of sports training in learning a complex technique. Particularly in combat sports, including taekwondo, strikes and kicks performed in place, in a jump or in rotation, as well as combinations, allow you to create effective technical and tactical actions. Both of them have a significant impact on the sports results achieved in competitions. The aim of this study is the knowledge about level of conditioning and coordination motor abilities of taekwondo ITF formula athletes.